Catalytic pyrolysis of polyethylene waste with Fuller's earth clay and metal oxides under mild conditions. (2022) - Mehdi, Muhammad Shozab; Mehran, Muhammad Taqi; Naqvi, Salman Raza; Zaman, Shafiq Uz; Khoja, Asif Hussain; Bahadar, Ali
Abstract: Numerous studies have been conducted to investigate the suitable processing of polyethylene into fuel using various clay catalysts but they were found to be less active and their yield was also lower than other catalysts such as Y zeolite. Furthermore, the heavier liquid products were obtained by utilizing clay catalysts. Keeping this point in view, the current investigation aimed to examine the aspects of catalytic degradation of polymer utilizing fuller's earth clay as the catalyst and various metal oxides as an additive. A series of experiments were carried out using three different catalysts. The plastic used was high-density polyethylene (HDPE) waste, whereas blended mixtures of (ZnO + Clay), (Fe(III)Oxide + Clay), and (Ni Oxide + Clay) were used as a catalyst. The plastic (HDPE) catalytically cracked under controlled conditions of 300 °C and 22 psi and in half-hour reaction time via cylindrical reactor (1 ft length, 0.5 ft diameter with a lid. The gaseous mixture produced during the catalytic degradation of the polymer was then analyzed in a gas chromatograph-mass spectrometer. The proportion of products i.e., propene, butyl isocyanide, and 1-pentene produced using clay and Fe (III) Oxide was higher compared to the other two catalysts. The concentration wt% of propene, butyl isocyanide, and i-pentene in the case of Fe (III)Oxide + Clay catalyst were 55.10 wt%, 30.10 wt%, and 15.30 wt% as compared to ZnO + Clay catalyst and Ni Oxide + Clay catalyst which contain amounts lower than Fe(III)Oxide + Clay catalyst. This was primarily due to milder acidity and high active sites of the Clay + Fe (III) Oxide catalyst. Furthermore, the experimental setup developed in this work appeared to be feasible to produce low molecular weight hydrocarbons.